2013
DOI: 10.1063/1.4813500
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric mechanism of croconic acid: A first-principles and Monte Carlo study

Abstract: The ferroelectric mechanism of croconic acid in terms of the electronic structure and the molecular structure was studied by first principles using the density functional theory with the generalized gradient approximation. The spontaneous polarization (Ps) was simulated by the Berry phase method. It is found that the large polarization originates from charge transfer due to the strong "push-pull" effect of electron-releasing and -withdrawing groups along the hydrogen bond. According to the characteristics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The vector symbols in Fig. 1(a) denote the structural distortions in CA crystal from its hypothetical paraelectric phase to the FE ground state, with Pbcm and Pca2 1 space group symmetry respectively 20,29,30,45 . Clearly the distortions are dominated by proton transfer as evidenced by the large displacements of protons along the H-bonding directions threading oxygen atoms on two neighboring molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector symbols in Fig. 1(a) denote the structural distortions in CA crystal from its hypothetical paraelectric phase to the FE ground state, with Pbcm and Pca2 1 space group symmetry respectively 20,29,30,45 . Clearly the distortions are dominated by proton transfer as evidenced by the large displacements of protons along the H-bonding directions threading oxygen atoms on two neighboring molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Such intriguing physics originates from the unusual way in generating FE. For CA, the polar distortion arises from the large displacements of protons, which is conceptually described as the proton transfer mechanism 10,22,29 . When a proton is located at the middle point of two oxygen atoms along an H-bond, the two molecules formed a symmetric H-bond environment.…”
Section: Introductionmentioning
confidence: 99%
“…5. The distance between the oxygen atoms (i.e., O1 and O2) was reduced from 2.53 ± 9.81 × 10 −4 Å to 2.50 ± 2.26 × 10 −3 Å after the proton-beam irradiation using the defined formula (9). Therefore, the average distance between the two equilibrium positions of the hydrogen atoms is expected to decrease in proportion to the distance between the oxygen atoms 23 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of hydrogen embedded in a solid lattice, the ferroelectric phase of hydrogen-bonded ferroelectrics usually exists at temperatures below 0 °C 8 . Recently, several studies reported that organic molecular crystals such as croconic acid, H 2 C 5 O 5 , switched their polarity exhibiting ferroelectricity with a high spontaneous polarization of 21 μC/cm 2 at room temperature 9 . It was found that the large polarization originates from the collective site-to-site transfer of protons along the hydrogen-bonded networks 10 .…”
Section: Microscopic Difference Of Hydrogen Double-minimum Potential mentioning
confidence: 99%
“…This research has the objective of obtaining nanomultiferroic materials with good electric polarization properties with the addition of ferroelectric materials (BTO) into multiferroic materials (BFO). Good electric polarization properties could increase the opposite response when given external effects such as magnetic fields, electric fields or stresses / strain [8]. It means could improve multiferroic properties (increase ME coupling constant).…”
Section: Introductionmentioning
confidence: 99%